2004
DOI: 10.1161/01.hyp.0000143850.73831.9d
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) Inhibitory Mechanism of Norepinephrine Release in Hypertensive Rats

Abstract: Abstract-Release of norepinephrine (NE) by the hypothalamic nuclei may contribute to regulation of sympathetic nervous system (SNS) activity. Angiotensin-(1-7) [Ang-(1-7)] has an antihypertensive effect and may decrease SNS activity. We tested the hypothesis that Ang-(1-7) inhibits the release of NE in hypothalami, via the Ang-(1-7) and angiotensin II type 2 (AT 2 ) receptors, acting through a bradykinin (BK)/NO-dependent mechanism. Hypothalami from normotensive controls and spontaneously hypertensive rats (SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 39 publications
2
78
1
Order By: Relevance
“…23 Additional evidence suggests that Ang-(1-7) reduces the release of norepinephrine acting through a BK/ nitric oxide-mediated mechanism that stimulates cGMP/ protein kinase G signaling. 24 Other experiments also point to an interrelationship between Ang-(1-7) and the prostaglandin-BK-nitric oxide system. In the spontaneously hypertensive rat (SHR), the vasodilator effects of Ang-(1-7) are blocked in the presence of the cyclooxygenase 1 inhibitor, indomethacin, 25 confirming previous findings in which the vasorelaxing response of canine coronary artery ring induced by Ang-(1-7) was abolished by the BK antagonist icatibant, 26 whereas the peptide also inhibited the degradation of 125 I-[Tyr 0 ]-BK and the appearance of BK-(1-7) and BK-(1-5) metabolites in the effluent from the preparation.…”
Section: Formation and Functions Of Ang-(1-7)mentioning
confidence: 97%
“…23 Additional evidence suggests that Ang-(1-7) reduces the release of norepinephrine acting through a BK/ nitric oxide-mediated mechanism that stimulates cGMP/ protein kinase G signaling. 24 Other experiments also point to an interrelationship between Ang-(1-7) and the prostaglandin-BK-nitric oxide system. In the spontaneously hypertensive rat (SHR), the vasodilator effects of Ang-(1-7) are blocked in the presence of the cyclooxygenase 1 inhibitor, indomethacin, 25 confirming previous findings in which the vasorelaxing response of canine coronary artery ring induced by Ang-(1-7) was abolished by the BK antagonist icatibant, 26 whereas the peptide also inhibited the degradation of 125 I-[Tyr 0 ]-BK and the appearance of BK-(1-7) and BK-(1-5) metabolites in the effluent from the preparation.…”
Section: Formation and Functions Of Ang-(1-7)mentioning
confidence: 97%
“…[3][4][5] In a study we presented earlier, the change in NE release induced by BK was investigated in the hypothalamus of normotensive and hypertensive rats. 6,7 In an in vitro study using rat brain slices, we showed that BK increased the stimulation-evoked NE release in a dose-dependent manner.…”
Section: To the Editormentioning
confidence: 99%
“…In addition, the inhibitory effect of Ang-(1-7) was also blocked in the presence of an inhibitor of nitric oxide synthesis, suggesting that endogenous BK is mediating nitric oxide release, and in this way Ang-(1-7) diminishes NE release. 4 Therefore, since central endogenous levels of BK are very low, 1 a synergistic effect between BK and Ang-(1-7) on NE release is not expected, as Dr Tsuda suggested. On the other hand, synergy means "working together", 5 so we would not expect to see a synergistic effect between Ang-(1-7) and BK on NE release when they have an antagonistic effect on that mechanism.…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 It was demonstrated that Ang-(1-7) and bradykinin can interact to modulate baroreflex control of the heart rate, suggesting that the centrally modulatory effect of Ang-(1-7) on the baroreflex might be mediated, at least in part, by the release of kinins. 2 Gironacci et al 4 demonstrated that Ang-(1-7) decreased K + -induced norepinephrine release in the hypothalamus of spontaneously hypertensive rats by the nitric oxide and bradykinin B2 receptor-dependent mechanisms. It can be speculated that the interactions between Ang-(1-7) and bradykinin might have a crucial role in the central modulation of BRS.…”
mentioning
confidence: 99%